Working Productivity Analysis on the Process of Drying Fish Using Solar Dryers - I Gede Santosa; I Gede Bawa Susana (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2021)
The process of drying fish using solar energy is strongly influenced by weather conditions. Sunlight is needed by household scale workers because it is cheap. On the other hand, sun drying creates additional workload for workers. Workers are exposed to hot sun during drying. Continuous heat exposure results in an increased work pulse. This affects the level of worker productivity. To anticipate this, a solar dryer is used by utilizing a solar collector as an absorber of sunlight and a drying chamber for the drying process of fish. The use of solar dryers has been shown to increase drying temperatures and reduce workers' sun exposure. This decreases the workload of workers, so that it has an impact on increasing productivity. Worker productivity increased by 133.94%.